Smartphone-based supportive counseling to reduce pregnancy-specific stress in pregnant adolescents - Ulfah, Mariah; Yusuf , Munawir (Universitas Muhammadiyah Purwokerto, 2025)
Background: Adolescence is a psychologically vulnerable period, and pregnancy during this stage increases the risk of stress, particularly when pregnancies are unintended or accompanied by social stigma. Although psychosocial support is essential, evidence on supportive counseling specifically for pregnant adolescents is limited, and most interventions rely on traditional face-to-face methods. To address this gap, this study developed a smartphone-based supportive counseling model to strengthen maternal mental health among Indonesian adolescents. Purpose: To examine the effect of smartphone-based supportive counseling on pregnancy-specific stress among pregnant adolescents. Methods: A quasi-experimental pre- and post-test non-equivalent control group design was used involving 60 pregnant adolescents. Participants were assigned to an intervention group (n = 30) or a control group (n = 30) using purposive sampling. The intervention group received smartphone-based supportive counseling sessions (60–120 minutes) over three weeks, while the control group received routine antenatal care. Pregnancy-specific stress was measured before and after the intervention. Data were analyzed using paired t-tests and independent t-tests. Results: The intervention group showed a significant reduction in pregnancy-specific stress after supportive counseling (p < 0.001), whereas the control group showed no significant change (p = 0.069). Conclusion: Smartphone-based supportive counseling is effective in reducing pregnancy-specific stress among pregnant adolescents and may serve as an accessible psychosocial support model in resource-limited settings.